Robotic single-site cholecystectomy for a symptomatic duplicated gallbladder - Pamela K. Mar, MD; Gail E. Besner, MD; Shamlal Mangray, MBBS; Sally Smith, DO; Karen A. Diefenbach, MD (Elsevier, 2020)
Duplicated gallbladders are relatively rare congenital anomalies. Their unique anatomy provides anatomical challenges that should be considered at the time of imaging and at the time of surgery. We present a case report of a patient with biliary colic who was found to have a duplicated gallbladder on imaging. This is the first reported pediatric patient to have undergone a robotic single-site cholecystectomy for a duplicated gallbladder. Keywords: Duplicated gallbladder, Robotic cholecystectomy, Single-site cholecystectomy